anonymous
  • anonymous
Help please!! Much appreciated! Solve each system by any method of your choice: 2x-5y=-1 4x-5y=-7
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
some say elimination is easiest
anonymous
  • anonymous
you can exchange rows 4x-5y=-7 add -1*r2 into r1 2x-5y=-1
anonymous
  • anonymous
So then the 5's would cancel out?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
i mean -2 times r2 into r1
anonymous
  • anonymous
you could also do that too C but i rather start from the outer left most variable.
anonymous
  • anonymous
4x-5y=-7 add 1*r2 into r1 2x-5y=-1 6x=-8 2x-5y=-1
anonymous
  • anonymous
Oh my gosh, I am so sorry, my computer shut down on me! haha(: Thank you!
anonymous
  • anonymous
6x=-8 2x-5y=-1 from here you know x=-8/6=-4/3 and you can plug that into the bottom equation 2(-4/3)-5y=-1 and solve for y
anonymous
  • anonymous
i think it looks wrong let me do it again.
anonymous
  • anonymous
2x-5y=-1 4x-5y=-7 add -1r2 to r1 -2x = 6 4x-5y=-7 I see now so -2x=6 is x=-3 now plug that into second equations 4x-5y=-7 4*-3-5y=-7
anonymous
  • anonymous
-12-5y=-7 -5y=5 y=-1
anonymous
  • anonymous
Haha(: Thank you so much! Much appreciated!! GBU!! :)
texaschic101
  • texaschic101
2x - 5y = -1 -->(-1)2x - 5y = - 1 4x - 5y = - 7 --------------- -2x + 5y = 1 (result of multiplying by -1) 4x - 5y = - 7 ----------------add 2x = -6 x = 6/-2 x = -3 now sub -3 in for x in either of the equations 4x - 5y = - 7 4(-3) - 5y = - 7 -12 - 5y = - 7 -12 + 7 = 5y - 5 = 5y -5/5 = y -1 = y check... 2x - 5y = - 1 2(-3) - 5(-1) = - 1 -6 + 5 = - 1 -1 = -1 (correct) ANSWER : x = - 3, y = -1 or (-3,-1)
anonymous
  • anonymous
Wow! haha(: Thanks so much! Such a bug help!! GBU!!
anonymous
  • anonymous
*big :P

Looking for something else?

Not the answer you are looking for? Search for more explanations.